Unethical practices in the interactive sales environment: – A framework and agenda for future research. - Ameer Irfan; Halinen Aino (Bournemouth, 2022)
Purpose: The purpose of this review paper is to provide an overview of the unethical practices of key stakeholders involved in the sales environment.
Method: We systematically reviewed 103 relevant articles published in 28 scholarly business journals from the beginning to June 2013.
Results: We identified four key stakeholders (management, coworkers, customers and competitors) involved in the sales environment whose unethical practices have been considered relevant for sales person’s own ethical behavior. Most of the studies dealt with sales person‐driven unethical practices in relation to management and customers. By reviewing existing knowledge, we propose a framework to understand interactive macro ethical sales environment.
Theoretical implications: The framework opens up a holistic, interactive and contextual view on a sales person’s ethical behavior complementing the traditional positive ethical decision making research in sales. We also identify several research gaps in this domain and propose avenues for future research.
Practical implications: Better knowledge about unethical practices of key stakeholders in macro sales environment may help firms to control unethical practices and minimize their impacts. Review can also help sales academics and practitioners in developing better questionnaires and ethical scenarios for sales ethics’ education, training and research.
47th Academy of Marketing Conference